COVID-19 and post COVID-19 financing of MSMEs: a case of Johannesburg - Tshehla, Kgaogelo (Graduate School of Business (GSB), 2026)
Micro, small and medium enterprises (MSMEs) are widely accepted as the backbone of economic growth and contribute towards job creation and poverty alleviation. The role that MSMEs can play is amplified in South Africa, given the poor performance of the economy, high levels of inequality and unemployment. The government has instituted several initiativesand policies aimed at fostering the growth of MSMEs. However, despite these efforts, MSMEs find themselves facing various challenges, including access to finance. COVID- 19 threatened the survival and any growth prospects for MSMEs, but also prompted policy alterations in response to the crisis, aimed at delivering relief measures for the MSMEs. Therefore, this dissertation explored the impact of the COVID-19 policy responses on financing MSMEs in South Africa. Specifically, the study sought to understand the impact of COVID- 19 on the financing of MSMEs in based in Johannesburg and the benefits and challenges that MSMEs experienced in their attempt to obtain debt relief or access to finance. The dissertation employed a qualitative research approach in which primary data is collected from participants through interviews with MSMEs in Johannesburg, South Africa. The results of the thematic analysis found that financing options were required to support MSMEs with employee relief and retention, decrease in productivity, cash flow and supply chain issues, and information and communications technology (ICT) adoption. MSMEs encountered difficulties in trying to access finance, despite the credit guarantee schemes made available to them. A sentiment emerged that banks and government agencies exhibited a reluctance to attentively address the distinctive challenges faced by these enterprises, consequently constraining their ability to effectively communicate and navigate their specific circumstances. MSMEs also realized the importance of a compliant business as a prerequisite for accessing financial resources. An additional revelation pertained to the imperative of cultivating business resilience as a strategic imperative for enduring comparable crises should they transpire. The results also found that there were some benefits and challenges that MSMEs experienced when exploring their financing options. The thematic analysis identified two key benefits that MSMEs experienced in their attempt to obtain debt relief or access finance during the pandemic. These included the increased resilience and diversification of MSMEs. The two main challenges that MSMEs experienced where the inability to access employee relief schemes and access finance. It is recommended that MSMEs be educated on bank processes and requirements, business management, financial literacy and alternative sources of finance so as to illustrate the profitability of their business more accurately and understand credit affordability metrics. It is also recommended that financial institutions make better use of the credit guarantee schemes and improve take- up on the funds available from these schemes.